Hygiene: textbook - Мельниченко, П. И. военная медицина, гигиена 19480901 Павел Иванович (Textbook, 2021)
The textbook represents the characteristics of the current status of the science, demonstrates the evolution of hygiene at various historical stages, and considers the problems of hygienic signifi cance, environment, and human ecology. Much attention is paid to health, algorithm of hygienic diagnostics which allows to detect changes in the human health status at the donozological (pre-pathological) level, as well as in the information on the administrative and legal forms of control over prophylactic arrangements and the health security system for each person. The textbook is intended for students of medical higher educational institutions and university departments majoring in General Medicine, Dentistry and Pharmacy.